2004
DOI: 10.1111/j.1526-4610.2004.446010.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Cluster Headache

Abstract: The data closely approximate those of Chervin et al, where 80% had RDI > 5. The relationship sleep apnea has in the perpetuation or precipitation of cluster headache is still to be determined. There are some reports that treatment stops the cluster but there is no prospective study. The high incidence (80.64%) seen in this population suggests the cluster patient should receive a sleep evaluation and perhaps intervention with continuous positive airway pressure (CPAP) or an appropriate dental device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 16 publications
3
48
0
Order By: Relevance
“…Chervin et al [26] recruited patients with CH and reported that 80% of them had an Apnea/Hypopnea Index of more than 5. Similar fi gures were found in a study done by Graff-Radford and Newman [27], in which 80.64% of the 31 patients diagnosed with ECH also suffered from sleep apnea. More recently, Nobre et al [28] reported a higher prevalence of sleep apnea in patients with CH when compared with the control group (58.3% vs 14.3%, respectively).…”
Section: Discussionsupporting
confidence: 82%
“…Chervin et al [26] recruited patients with CH and reported that 80% of them had an Apnea/Hypopnea Index of more than 5. Similar fi gures were found in a study done by Graff-Radford and Newman [27], in which 80.64% of the 31 patients diagnosed with ECH also suffered from sleep apnea. More recently, Nobre et al [28] reported a higher prevalence of sleep apnea in patients with CH when compared with the control group (58.3% vs 14.3%, respectively).…”
Section: Discussionsupporting
confidence: 82%
“…A study of 37 cluster headache patients who underwent polysomnography identified an 8.4-fold increase in the incidence of obstructive sleep apnea relative to age-and gender-matched controls (58% vs 14%, respectively), and this risk increased over 24-fold among patients with a body mass index greater than 25 kg/m 2 [24]. This marked increase in the incidence of sleep apnea among cluster headache patients had been reported in earlier research [25,26], and treatment of sleep apnea had been observed to improve cluster headache control [25]. Cluster headache attacks observed on polysomnography were linked to REM sleep [14], at least in cases of episodic cluster, although perhaps not for patients having the chronic form of cluster headache [27].…”
Section: Cluster and Other Trigeminal Autonomic Cephalalgiasmentioning
confidence: 68%
“…A study of 37 cluster headache patients who underwent polysomnography identified an 8.4-fold increase in the incidence of OSA relative to controls matched for age and gender (58% vs 14%), and this risk increased more than 24-fold among patients with a body mass index (BMI) greater than 25 kg/m 2 [15]. Another uncontrolled study of 31 cluster headache patients who underwent polysomnography observed OSA in 80% (25/31) of these patients [16]. Likewise, Sand et al [17] reported that patients with OSA were seven times more likely to have chronic headache than the general population.…”
Section: Sleep Disorders Associated With Headachementioning
confidence: 94%